Ablative fractional carbon dioxide laser improves quality of life in patients with extensive burn scars: A nested case–control study. Issue 9 (18th September 2022) - Liu, Huazhen; Shu, Futing; Xu, Haiting; Ji, Chao; Wang, Yuxiang; Lou, Xiaozhen; Luo, Pengfei; Xiao, Shichu; Xia, Zhaofan; Lv, Kaiyang
Abstract: Background and Objectives: Ablative fractional carbon dioxide laser (CO2 ‐AFL) for small‐area burn scar management shows encouraging outcomes. Few studies, however, focused on comprehensive outcomes following CO2 ‐AFL treatment for extensive burn scars. This study evaluated whether CO2 ‐AFL surgery improved the quality of life (QoL) for burn survivors with extensive hypertrophic scars. Methods: A retrospective nested case–control study was initiated to analyze the efficacy of CO2 ‐AFL treatment for patients with large‐area burn scars. Patients with extensive burn scars (≥30% total body surface area [TBSA]) were registered in our hospital from March 2016 to October 2018. Patients undergoing CO2 ‐AFL surgery were divided into CO2 ‐AFL group, and patients undergoing conventional surgery were matched in a 1:1 ratio as the conventional surgery group according to the burned area. The questionnaires were collected and followed up. The 36‐Item Short Form Health Survey (SF‐36) and Burns Specific Health Scale–Brief (BSHS‐B) were the primary parameters. Secondary parameters included the Pittsburgh Sleep Quality Index (PSQI), University of North Carolina "4P" Scars Scale (UNC4P), Patient Scars Assessment Scale for Patient (POSAS‐P), and Douleur Neuropathique 4 questions (DN4). Results: 23 patients (55.96 ± 21.59% TBSA) were included in CO2 ‐AFL group and 23 patients (57.87 ± 18.21% TBSA) in conventional surgery group. Both the BSHS‐B total score (CO2 ‐AFL vs. conventional surgery: 115.35 ± 29.24 vs. 85.43 ± 33.19, p = 0.002) and the SF‐36 total score (CO2 ‐AFL vs. conventional surgery: 427.79 ± 118.27 vs. 265.65 ± 81.66, p < 0.001) for the CO2 ‐AFL group were higher than those for the conventional surgery group. Parameters for the CO2 ‐AFL group were lower than those for the conventional surgery group in all of the following comparisons: PSQI total score (CO2 ‐AFL vs. conventional surgery: 7.70 ± 3.74 vs. 12.26 ± 4.61, p = 0.001), POSAS‐P total score (CO2 ‐AFL vs. conventional surgery: 26.48 ± 6.60 vs. 33.04 ± 4.56, p < 0.001), UNC4P total score (CO2 ‐AFL vs. conventional surgery: 5.57 ± 1.97 vs. 7.26 ± 1.81, p = 0.004), and DN4 score (CO2 ‐AFL vs. conventional surgery: 3 [2–5] vs. 5 [4–8], p = 0.004). Conclusions: Compared to conventional surgery, whole scar CO2 ‐AFL surgery dramatically improved physical and mental health as well as QoL for people with extensive burn scars. Additionally, CO2 ‐AFL enhanced the evaluation of scars including their appearance, pain, itching, and a host of other symptoms.